Evaluation of the causes and maternal and fetal complications in prolonged pregnancy compared with term pregnancy in Sanandaj Besat hospital during 2013-2014 - Shamsi Zare; Farnaz Zandvakili; Nasrin Soofizade; Fariba Farhadifar; Amin Sadrinezhad (Mashhad University of Medical Sciences, 2017)
Introduction: Prolonged pregnancy occurs in approximately 10% of pregnancies which can also have consequences for the mother and fetus. Since there is no statistical evaluation of the outcome of prolonged pregnancy compared with term pregnancies in Sanandaj city, this study was performed with aim to evaluate the risk factors associated with prolong pregnancy and management of them. Methods: This analytic-descriptive study was performed with evaluation of the files of all referring pregnant women and determining the prevalence of prolong pregnancy in Sanandaj Besat hospital during 2013-2014. Then, in this population, the variables of prolonged pregnancy compared to term pregnancy were collected. Finally, these two types of pregnancy were compared in terms of frequency of the number of pregnancy, the number of delivery, maternal BMI, reduction in amniotic fluid, use of misoprostol for cervical ripening, uterine atony, response to induction, mode of delivery, decelerations of fetal heart rate, Liquid Disposal, birth weight, 1 and 5 minute Apgar scores, and NICU admission. Data were analyzed by SPSS software (version 20) and Chi-square and T tests. P<0.05 was considered significant. Results: Prolonged pregnancy compared with term pregnancy was significantly different in terms of maternal and neonatal complications such as the number of pregnancy, the number of delivery, use of misoprostol for cervical ripening, uterine atony, response to induction, mode of delivery (vaginal or cesarean), decelerations of fetal heart rate, the response rate to induction, decelerations of fetal heart rate, birth weight, and 1 minute Apgar score (P <0.05), but there was no significant difference in terms of maternal BMI, reduction in amniotic fluid, Liquid Disposal, 5 minute Apgar score, and NICU admission (P>0.05). Conclusion: Maternal and fetal risk factors were significantly higher in prolonged pregnancies than in term pregnancies. Therefore, it is essential to use guidelines for dealing with long-term pregnancies to maintain the health of mother and neonate.